ANALISIS KESESUAIAN PENGUKURAN KALORI SMARTWATCH DENGAN PERHITUNGAN MET PADA AKTIVITAS OLAHRAGA - Raihan, Rafli Assiddiqie; Paputungan, Irving Vitra; Setiawan, Mukhammad Andri (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2026)
This study aims to evaluate the agreement between calorie estimations generated by smartwatches and manual calculations based on the Metabolic Equivalent of Task (MET) during physical activity. Three participants with different physiological characteristics and activity intensities completed 15 training sessions using the Xiaomi Smart Band 8 and 10. Calorie estimates from the devices were compared with MET-based calculations using the paired sample t-test. The results indicate that, for moderate to high intensity activities such as jogging and running, no significant differences (p > 0.05) were observed between the two estimation methods, suggesting a good level of agreement. Conversely, low-intensity walking showed significant differences (p < 0.05), reflecting a tendency for overestimation by the smartwatch. Overall, the agreement improved when heart rate rhythm and movement patterns were more stable, consistent with physiological principles relating oxygen consumption and MET values. As a preliminary case-series, this study highlights the importance of activity intensity when interpreting smartwatch-based energy estimates and provides insight into the practical use of wearable devices for daily exercise monitoring.